Lung ultrasound in optimizing management of patients with heart failure: current status and future prospects - Zh. D. Kobalava; A. F. Safarova; E. V. Kokhan; M. R. Islamova (Российский кардиологический журнал, 2020)
The review discusses the prognostic value and contribution to therapy optimization of lung ultrasound for heart failure patients.